Preferensi Pembelian Kosmetik Halal Generasi Z: Peran Halal Image, Religiusitas, Gaya Hidup, dan Media Sosial - Ade Adhariah; Budi Sudrajat; Hadi Peristiwo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The rapid growth of Indonesia’s cosmetic industry has heightened attention to halal aspects, particularly among Muslim Generation Z who are active in digital platforms. This study examines the influence of halal image, religiosity, and halal lifestyle on cosmetic purchase preference, with social media as a moderating variable. A quantitative survey using a Likert-scale questionnaire was distributed to respondents aged 18–27 years in South Tangerang City, and data were analyzed with Structural Equation Modeling (SEM) using SmartPLS. Results indicate that social media plays a dominant descriptive role but is not statistically significant as a moderator, while halal image, religiosity, and halal lifestyle show no significant effect on purchase preference. These findings suggest the need for developing new constructs that better capture the digital consumption behavior of Generation Z.